Evaluation of the benefit of rivaroxaban on VOYAGER PAD primary composite of limb, heart and brain outcomes using the global rank and win ratio methods. (3rd October 2022) - Bonaca, M; Debus, S; Nehler, M; Anand, S; Patel, M; Pap, A F; Deng, H; Hodge, S; Szarek, M; Haskell, L; Muehlhofer, E; Berkowitz, S; et al.
Abstract: Background/Introduction: The VOYAGER PAD trial demonstrated that rivaroxaban 2.5 mg twice daily added to background antiplatelet therapy reduced a composite of irreversible harm events of the heart limb and brain versus placebo in patients with symptomatic peripheral artery disease (PAD) after lower extremity revascularization. The primary analysis was performed as time to first event with equal weighting of components including fatal and non-fatal events. Purpose: Traditional time to event analyses of composites generally assess outcomes with equal weights. Analyses evaluating outcomes using ranked or weighted methods may provide clinicians a mechanism to interpret results including different weighting and enable shared decision making with patients. Methods: Exploratory analyses of the primary composite outcome were prespecified prior to trial completion/database lock. Two previously described approaches to evaluate composite outcomes by ranking or weighting were utilized. The first was the global rank method which includes ranking all components of the composite by order of clinical importance (Table 1) with a primary and alternative ranking prespecified. Each patient is assigned a rank with the worse rank for worse outcome and for patients with the same outcome, those occurring earlier assigned the worse rank. Van Elteren test for differences between groups was applied stratified by type of procedure and clopidogrel use consistent with the primary trial analysis. The second was the unmatched win ratio method according to Pocock's rule which ranked CV death higher than non-fatal events and then compared pairs of subjects, one from each treatment group for wins and losses for wins and losses as outlined in Table 1. Finkelstein and Schoenfeld statistics were utilized with confidence intervals provided from bootstrapping. Results: A total of 6564 patients were randomized and all outcomes through the common study end date were counted. The global rank method using both the primary and alternative method yielded a statistically significant superior effect of rivaroxaban versus placebo (p-value for primary ranking 0.0158, p-value for alternative ranking 0.0155). When using the win-ratio approach, there were more wins for rivaroxaban (14.8%) than placebo (12.8%) with 72.4% of patients having no primary component events (Figure 1). The overall win ratio was 1.16 95% CI (1.03–1.30) in favor of rivaroxaban with p=0.0167. Conclusion(s): Rivaroxaban significantly reduces acute limb ischemia, amputation, MI, ischemic stroke or CV death in PAD after lower extremity revascularization. Exploratory analyses of this efficacy composite show consistent superiority either when considered as a ranked hierarchy of outcomes with CV death as the worst or whether considering a win-ratio approach ranking CV death as worse followed by non-fatal events. These data support the robustness of the primary trial results when considering ranking of the composite components. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Bayer